TINDAK TUTUR ILOKUSI DALAM WAWANCARA TGH. MUHAMMAD ZAINUL MAJDI PADA TALKSHOW “MATA NAJWA” - Azanul Islam (Center of Language and Cultural Studies, 2017)
The objective of this study is to see illocution speech acts in an interview of the governor of Nusa Tenggara Barat in Mata Najwa talkshow. This study used content analysis as design and used transcript of the interview as source of data. Data were analyzed using qualitative approach describing kinds of illocutionary acts used by the interviewer and interviewee. The findings of the study were all illocution appeared in the interview: assertive, directive, commissive, expressive, and declarative. Assertive binds speakers of truth on what it says. Directives are done with the intention that the hearers do the act referred to in the speech. Expressives function as an evaluation of the things mentioned in the speech. Declaratives state the commitmenet to status of being new.